Deficiênciade coenzima Q10: caracterização clínica, bioquímica e molecular - Miyadahira, Juliana Harumi Arita [UNIFESP] (2018)
Objective: to identify patients with suspected coenzyme Q10 deficiency (CoQ10) and make a clinical, biochemical and molecular characterization of these patients. Methods: twenty seven patients between 0 and 17 years old from Child Neurology and General Neurology and Ataxias clinics of Universidade Federal de São Paulo, with clinical suspicion of CoQ10 deficiency were selected and evaluated by our group of neurologists. They were submitted to preestablished complementary exams and classified according to one of the classic CoQ10 deficiency phenotypes. Biochemical studies (CoQ10 content, mitochondrial complexes, oxidative stress measurements, citrate synthase dosage, glutathione peroxidase activity and mitochondrial DNA quantification) were performed on skin fibroblasts. Total CoQ10 skin fibroblasts was measured by HPLC / ECD. Mitochondrial complexes, citrate synthase activities and glutathione peroxidase were measured by spectrophotometry. Oxidative stress was measured by cell marking of superoxide anions with MitoSOX kit. Quantification of mitochondrial DNA was obtained by normalizing its quantity by the single copy of the B2M gene. Molecular analyzes by exome sequencing were performed in those with low CoQ10 levels compared to controls or with suggestive biochemical profile. Statistical analysis was applied to the biochemical tests using oneway ANOVA followed by Bonferroni adjustment for multiple comparisons, considering p <0.05. Results: five out of twenty seven patients had CoQ10 deficiency. Patients with CoQ10 deficiency presented variable activities of mitochondrial complexes. Citrate synthase activity was increased to 3 of them. The generation of superoxide anions was increased to 2 patients suggesting mitochondrial dysfunction. Molecular analysis could identify secondary CoQ10 deficiencies.